Mimesis as philosophy of religion - Parrilla Martínez, Desiderio (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
This article shows the evolution of mimetic theory as philosophy of religion, the great contribution of René Girard. It involves an analysis «in actu nascente» about fundamental thesis of girardian system, giving the biographical and academic foundations. It reflects, in this way, the theoretical influences and precedents of his research. René Girard, desire, mimetic theory, Christianity